Irrigation management transfer : worldwide efforts and results - Garces-Restrepo, Carlos; Munoz, Giovanni; Vermillion, Douglas L.; Food and Agriculture Organization of the United Nations (Rome : Food and Agriculture Organization of the United Nations, 2007)
The present water report is the final product emanating from efforts by FAO, IWMI and others to document and understand the implications of the irrigation sector embarking on a wide reform process. It is intended to be a knowledge synthesis document that captures the global experiences emerging from a wide-reaching process targeting the reform of the irrigation sector. This study indicates that irrigation management transfer (IMT) is an approach for irrigation sector reform with the potential to improve the sustainability of irrigation systems.The process requires inter alia strong political commitment, negotiations among stakeholders, and long-term capacity development. Irrigation management transfer should not be seen as a process that has a clear "beginning" and "end". While the former can be more easily identified, the latter is much more difficult to determine. In fact, IMT can be the initial stage of an evolving long reform process. The accompanying CD-ROM contains IMT country profiles and case studies, an international IMT e-mail conference, a bibliography and links.--Publisher's description.
Introduction -- Policy and legal framework for irrigation management transfer -- Implementing irrigation management transfer -- Results of irrigation management transfer -- Integrating lessons learned into future interventions.
"TC/M/A1520E/1/12.07/1600"--P. [4] of cover.
Includes bibliographical references (pages 53).
Mode of access: World Wide Web.
System requirements: Adobe Acrobat Reader.
Description based on print version record; resource not viewed.
Keywords: Irrigation -- Management; Technology transfer